197k views
2 votes
Factories 4a² - 6ab​

User EKS
by
5.0k points

2 Answers

5 votes
4a^2-6ab
=(2a)^2-6ab

by completing the square

=(2a)^2-(2*2a*3b/2)+(3b/2)^2-(3b/2)^2

=(2a-3b/2)^2-(3b/2)^2
=(2a-3b/2+3b/2)(2a-3b/2-3b/2)
{Since a^2-b^2= (a-b)(a+b)}
=(2a)(2a-3b) (Ans)
User Dndr
by
5.7k points
6 votes

Answer:


2a(2a-3b)

Explanation:

4 and 6 have a common factor 2.


a^2 and
ab have a common factor
a.

So we can factor out
2a:


4a^2-6ab


2a((4a^2)/(2a)-(6ab)/(2a))


2a((2a(2a))/(2a)-(3b(2a))/(2a))


2a(2a-3b)

User Bitboy
by
5.2k points